The best practice of CRM implementation for small- and medium-sized enterprises - Michal Pohludka; Hana Štverková (Administrative Sciences, 2019)
The biggest key aspect to the success of a business is a satisfied customer. For this reason, it is possible to state that the growing trend of focusing on the customer and his/her needs has prevailed in recent years. The aim of this article is to analyze the use of CRM (Customer Relationship Management) systems in small- and medium-sized enterprises (SMEs) in the Czech Republic and to find the determinants for CRM system implementation. The best practice for CRM implementation suitable for SMEs is clarified using a specific case of a global enterprise. A fully functional CRM system can be considered a competitive advantage, and this is not only the case for global companies, but also for small and medium enterprises. Using a functional CRM interconnected with an ERP system, enterprises are able to manage business and direct marketing activities, as well as the company's overall profits. These functional systems lead to an integrated system called funnel management, which improves customer relationship management and leads to a sustainable business.
Keywords: 350; CRM; customer; funnel management; key account management; needs; segmentation; small- and medium-sized enterprises; sustainable business